Effector Mimics and Integrated Decoys, the Never-Ending Arms Race between Rice and Xanthomonas oryzae - Zuluaga, Paola; Szurek, Boris; Koebnik, Ralf; Kroj, Thomas; Morel, Jean-Benoit (Frontiers in Plant Science, 2017)
Plants are constantly challenged by a wide range of pathogens and have therefore evolved an array of mechanisms to defend against them. In response to these defense systems, pathogens have evolved strategies to avoid recognition and suppress plant defenses (Brown & Tellier 2011). Three recent reports dealing with the resistance of rice to Xanthomonas oryzae have added a new twist to our understanding of this fascinating co-evolutionary arms race (Ji et al. 2016; Read et al. 2016 and Triplett et al. 2016). They show that pathogens also develop sophisticated effector mimics to trick recognition.